2022
DOI: 10.5751/es-13200-270213
|View full text |Cite
|
Sign up to set email alerts
|

From stories to maps: translating participatory scenario narratives into spatially explicit information

Abstract: To understand future land use change, and related ecological and social impacts, scenario planning has become increasingly popular. We demonstrate an approach for translating scenario narratives into spatially explicit land use maps. Starting from four previously developed scenarios of land use change in southwestern Ethiopia we developed a baseline land use map, and rules for how to modify the baseline map under each scenario. We used the proximity-based scenario generator of the InVEST software to model the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We found that beneficiaries could be grouped into five clusters based on their ecosystem product rankings, and that these groups differed in their social–ecological context. Previous research had already shown that future development under different scenarios differed substantially between the four social–ecological kebele groups (Duguma et al., 2022). Smallholders in our study area, and in heterogeneous landscapes elsewhere, should thus not be treated as a homogeneous group, but rather differentiated based on their social–ecological context.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that beneficiaries could be grouped into five clusters based on their ecosystem product rankings, and that these groups differed in their social–ecological context. Previous research had already shown that future development under different scenarios differed substantially between the four social–ecological kebele groups (Duguma et al., 2022). Smallholders in our study area, and in heterogeneous landscapes elsewhere, should thus not be treated as a homogeneous group, but rather differentiated based on their social–ecological context.…”
Section: Discussionmentioning
confidence: 95%
“…To investigate the role of social–ecological context, the 78 kebeles (smallest administrative units in Ethiopia) in our study area were clustered into four social–ecological groups, based on a range of ecological and social variables, including land use and land cover data, altitude, remoteness and wealth. The pasture–cropland, the khat–cropland, the woody vegetation and the accessible–wealthy group were characterized, respectively, by high availability of pasture and arable land, by high availability of khat (a popular plant stimulant) and arable land, by high extent of woody vegetation cover and by being relatively accessible and wealthy (Duguma et al., 2022). We then selected eight kebeles—two from each social–ecological group (Figure 1, Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Brief summaries of the storylines of these scenarios are presented in Table 1 (for details see refs. 34,35). The scenarios considered a wide range of plausible environmental, social, and economic changes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Wang et al [68] adopted the InVEST model to probe the water yield, NPP, and soil conservation, and their results show that the NPP displays a trade-off relationship with respect to water yield, agreeing with our discoveries from the loess ridge, loess hilly, and covered sand, loess hilly areas (Figure 6). Moreover, other regions, such as arid watersheds in northwestern China [79], the Qinghai-Tibet Plateau [80], North America [81], Europe [82], and Africa [83], were also investigated using the InVEST model. Challenges still exist in this work and can be solved in our future work.…”
Section: Implications For Modeling Use and Policymakingmentioning
confidence: 99%